(3WHbGJ GdTGaYjI GdcHQis - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s ((3MSf Hf Ydj Hf YHjO Hf CMeO GdeQOGhj GdebOSj s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHhfUQ YHOGdhgGH GdSHcj GdTGaYj GdMeO ddg fMeOg hfSJYjfg s
(3BNQgG (B:s
(3hfGH ai GdbVGA HOeTb Yf bGVi eUQ hGdTGe CHj GdMSf Ydi Hf GdfYeGf Jhai ai TYHGf SfI NeS hSHYjf hKdGKeGFI s
(3hQOJ CjVkG JMJ YfhGf (B"(3GdedJbW ef WHbGJ GdTGaYjI GdcHQi hGdhSWi HQbe (B2068 (3JGQjNs
(3GfXQ (B313 (3, Qbe (B1126 (3JGQjNs
(3GdehLhO efgG GdLRA GdChd hjfJgi Edi Chd GdWHbI GdQGHYI s
(3fSNI NGeSI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJGQjNs